2020
DOI: 10.31764/orbita.v6i2.3365
|View full text |Cite
|
Sign up to set email alerts
|

Kepraktisan Panduan Praktikum Ipa Sederhana Sekolah Dasar (Sd) Berorientasikan Lingkungan Sekitar

Abstract: ABSTRAKPenelitian ini bertujuan untuk mengetahui tingkat keterpakaian produk yang dikembangkan dalam hal ini panduan praktikum IPA sederhana SD berorientasikan lingkungan sekitar. Jenis penelitian ini merupakan penelitian deskriptif. Panduan praktikum menjadi subyek dalam penelitian dan kepraktisan dari panduan praktikum yang dirancang sebagai objek penelitian. Pada penelitian ini tingkat kepraktisan diukur dengan menggunakan angket yang diberikan kepada siswa untuk melihat tanggapan siswa dalam penggunaan pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…The reason why students' learning motivation is not optimal in science is students' boredom in learning (Rahma et al, 2016). Other research by Darmayanti et al (2021) also found that more than 70% of students still had fairly good motivation. According to them, teachers, parents, and themselves are the determining factors for optimal student motivation.…”
Section: Introductionmentioning
confidence: 79%
“…The reason why students' learning motivation is not optimal in science is students' boredom in learning (Rahma et al, 2016). Other research by Darmayanti et al (2021) also found that more than 70% of students still had fairly good motivation. According to them, teachers, parents, and themselves are the determining factors for optimal student motivation.…”
Section: Introductionmentioning
confidence: 79%
“…Panduan praktikum IPA sederhana dengan alat dan bahan yang memanfaatkan lingkungan sekitar sebenarnya bisa dibuat sendiri oleh guru. Penelitian yang dilakukan oleh (Darmayanti, 2020), yang menyatakan bahwa panduan praktikum sederhana berorientasi lingkungan sekitar adalah panduan yang berisikan panduan tentang praktikum IPA yang sederhana, di mana alat dan bahan praktikum dapat memanfaatkan barang-barang yang ada di sekitar lingkungan kita.Untuk tempat praktikum, tidak selalu di laboratorium bisa saja di kelas atau pun di lingkungan sekitar. praktikum adalah suatu kegiatan dalam proses pembelajaran, di mana siswa melakukan observasi ataupun eksperimen secara langsung berkaitan dengan konsep materi yang dilakukan di laboratorium maupun di lingkungan sekitar (Djamarah, 2006).…”
Section: Pembahasanunclassified
“…The results of the students' response questionnaire to the practicum module are used as an indicator of the practicality of the practicum module. The purpose of the practicality analysis is to determine the level of usability of the developed product where the practicality data of the practicum module is obtained from filling out students' response questionnaires after using the practicum module (Darmayanti et al, 2020). The practicality of the practical module is presented in Table 5.…”
Section: Limited Trial Stagementioning
confidence: 99%
“…The green chemistry-based module that was developed got an average score of 86.23% in the very practical criteria. This means that the developed green chemistrybased practicum module can be used properly by students (Darmayanti et al, 2020). In addition, the existence of a practicum module can help students to achieve learning goals (Prabowo et al, 2016).…”
Section: Limited Trial Stagementioning
confidence: 99%